Gut microbes differ in postmenopausal women responding to prunes to maintain hip bone mineral density - Simpson, Abigayle M. R.; De Souza, Mary Jane; Damani, Janhavi; Rogers, Connie J.; Williams, Nancy I.; Weaver, Connie M.; Ferruzzi, Mario G.; Nakatsu, Cindy H. (Frontiers in Nutrition, 2024)
Foods high in phenolics such as prunes have been shown to exert protective effects on bone mineral density (BMD), but only certain individuals experience these benefits. This posthoc analysis of a 12-month randomized controlled trial aimed to identify the relationship among the gut microbiome, immune responses, and bone protective effects of prunes on postmenopausal women. Subjects who consumed 50-100g prunes daily were divided into responders (n=20) and non-responders (n=32) based on percent change in total hip bone mineral density (BMD, ≥1% or ≤-1% change, respectively). DXA scans were used to determine body composition and BMD.Immune markers were measured using immunoassays and flow cytometry. Targeted phenolic metabolites were analyzed using ultra performance liquid chromatography-tandem mass spectrometry. The fecal microbiota was characterized through 16S rRNA gene PCR amplicon sequencing. After 12 months of prune consumption, anti-inflammatory markers showed responders had significantly lower levels of IL-1β and TNF-α. QIIME2 sequence analysis showed that microbiomes of responders and non-responders differed in alpha (Shannon and Faith PD, Kruskal-Wallis p<0.05) and beta diversity (unweighted Unifrac, PERMANOVA p<0.04) metrics both before and after prune treatment. Furthermore, responders had a higher abundance of bacterial families Oscillospiraceae and Lachnospiraceae (ANCOM-BC p<0.05). These findings provide evidence that postmenopausal women with initial low BMD can benefit from prunes if they host certain gut microbes. These insights can guide precision nutrition strategies to improve BMD tailored to diet and microbiome composition.